Collision‐independent detection of molecular two‐photon excitation by time‐resolved parametric four‐wave mixing. (28th December 2015) - Stauffer, Hans U.; Wrzesinski, Paul J.; Roy, Sukesh; Kulatilaka, Waruna D.; Gord, James R.
Abstract : We report collision‐independent detection of gas‐phase nitric oxide (NO) via a two‐pulse, femtosecond (fs) time‐resolved parametric four‐wave‐mixing (PFWM) optical‐probe scheme. This approach exploits the broadband two‐photon excitation of rovibrational manifolds associated with resonant electronic molecular transitions, allowing species‐specific detection. The observed time‐domain fs‐PFWM spectral signature associated with this broadband electronic two‐photon excitation process is shown to exhibit negligible dependence on colliding‐partner concentrations at short (<10 ps) time delays, even in the presence of species that strongly quench excited‐state fluorescence. Furthermore, by employing a hybrid fs/ps PFWM scheme, the broadband two‐photon absorption spectrum of the molecular species of interest is demonstrated to be resolved in the wavenumber domain without need to scan the probe‐pulse delay. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We report collision‐independent detection of gas‐phase nitric oxide (NO) via two‐pulse, femtosecond (fs) time‐resolved parametric four‐wave‐mixing (PFWM). This approach exploits two‐photon broadband excitation of rovibronic manifolds, allowing species‐specific detection with negligible dependence on colliding‐partner concentrations at short (<10 ps) time delays, even in the presence of species that strongly quench excited‐state fluorescence. Using hybrid fs/ps PFWM, the broadband two‐photon absorption spectrum of the molecular species is spectrally resolved.